2016
DOI: 10.1186/s13293-016-0121-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in sympathetic innervation and browning of white adipose tissue of mice

Abstract: BackgroundThe higher prevalence of obesity-related metabolic disease in males suggests that female sex hormones provide protective mechanisms against the pathogenesis of metabolic syndrome. Because browning of white adipose tissue (WAT) is protective against obesity-related metabolic disease, we examined sex differences in β3-adrenergic remodeling of WAT in mice.MethodsEffects of the β3-adrenergic receptor agonist CL316,243 (CL) on browning of white adipose tissue were investigated in male and female C57BL mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 43 publications
8
80
0
2
Order By: Relevance
“…In addition to inflammation-induced remodeling, a sex difference in sympathetic activity results in female-specific induction of brown adipocytes in GWAT, which could be involved in the protection of female mice against metabolic disease [77]. Estrogen can also influence brown adipose tissue (BAT) activity by upregulating thermogenesis.…”
Section: Animal Models Identify Sex Differences In Adipose Tissue Biomentioning
confidence: 99%
“…In addition to inflammation-induced remodeling, a sex difference in sympathetic activity results in female-specific induction of brown adipocytes in GWAT, which could be involved in the protection of female mice against metabolic disease [77]. Estrogen can also influence brown adipose tissue (BAT) activity by upregulating thermogenesis.…”
Section: Animal Models Identify Sex Differences In Adipose Tissue Biomentioning
confidence: 99%
“…These differences could be the consequence of the different genetic basis of fat distribution between the sexes [29]. In addition, female mice are more responsive to recruitment of brown adipocytes in VAT than male mice, probably due to the higher level of estrogen-dependent sympathetic innervation [30]. One possible mechanism that could be behind the actions of ERβ in lipid homeostasis is the cross-talk between ERβ and PPARγ, where ERβ inhibits the ligand-mediated PPARγ activity that leads to reduced adipogenesis [8,11].…”
Section: Erβ In Visceral and Subcutaneous Adipose Tissuementioning
confidence: 99%
“…Estrogen signaling has been implicated in the regulation of thermogenic adipose tissue expression with both central nervous system and local effects in adipocyte progenitor cells (Lapid et al, 2014;Martinez de Morentin et al, 2014). For instance, it was shown that the induction of Ucp1 by CL-316,243 in mouse gWAT was compromised by experimental ovarian failure (Kim et al, 2016). Interestingly, the estrogen receptor is able to interfere with the activity of PPARg and thereby influence PPARgdependent metabolic processes (Foryst-Ludwig et al, 2008;Benz et al, 2012).…”
Section: Oxygen Consumptionmentioning
confidence: 99%